1987
DOI: 10.1159/000124739
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Effect of Insulin on Brain 5-Hydroxytryptamine Metabolism

Abstract: In this study we investigated the effect of insulin on striatal 5-hydroxytryptamine and tryptamine in streptozotocin-diabetic and in normal rats. Streptozotocin-diabetic rats show a reduction in rat striatal tryptophan, 5-hydroxytryptamine, and 5-hydroxyindole acetic acid, an effect observed at 7 or 14 days after the treatment began. In addition, the accumulation of striatal tryptamine in pargyline-treated rats was reduced at 14 days. Insulin administration produced an increase in rat striatal tryptophan conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
1

Year Published

1989
1989
1998
1998

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 3 publications
(8 reference statements)
1
9
1
Order By: Relevance
“…Th� most fre quent result reported has been a reduction in the cerebral tissue concentration of the 5-HT precursor tryptophan by 30--50% observed 1-4 weeks after intraperitoneal injection of STZ (Curzon and Fernando, 1977;Mackenzie and Trulson, 1978a;Trulson et aI., 1986). In contrast to these reports, according to which there were no alterations in the brain tissue levels of 5-HT or 5-HIAA, concentra tions of these were also reduced 2 weeks after in traperitoneal STZ treatment in the study of Kwok and Juorio (1987). In addition, a diminished synthe sis and turnover rate of cerebral 5-HT were found in rats with STZ-induced diabetes 2-3 weeks (Crandall et aI., 1981) and 4-6 weeks (Trulson et aI., 1986) after the injection.…”
Section: Discussioncontrasting
confidence: 68%
“…Th� most fre quent result reported has been a reduction in the cerebral tissue concentration of the 5-HT precursor tryptophan by 30--50% observed 1-4 weeks after intraperitoneal injection of STZ (Curzon and Fernando, 1977;Mackenzie and Trulson, 1978a;Trulson et aI., 1986). In contrast to these reports, according to which there were no alterations in the brain tissue levels of 5-HT or 5-HIAA, concentra tions of these were also reduced 2 weeks after in traperitoneal STZ treatment in the study of Kwok and Juorio (1987). In addition, a diminished synthe sis and turnover rate of cerebral 5-HT were found in rats with STZ-induced diabetes 2-3 weeks (Crandall et aI., 1981) and 4-6 weeks (Trulson et aI., 1986) after the injection.…”
Section: Discussioncontrasting
confidence: 68%
“…On the other hand, insulin has access to the brain, where it may act as a neuromodulator (32). Insulin has been shown to reduce cholinergic activity in cultured striatal neurons (33) and to accelerate the turnover of monoamines in the brain (34,35). Therefore, in hyperinsulinemic subjects, altered cholinergic and/or monoaminergic activity could account for cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Al though insulin also stimulates the central 5HT system [3], the physiological connections between central and EC cell-circulating 5HT systems have not been established. However, recent findings have demonstrated that medul lar vagal nuclei receive strong excitatory input arising front central 5HT nuclei [14.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin likewise activates central serotonerIt is a known fact that the administration of either glu-gic and parasympathetic systems [3,4], Nonetheless, how cose or insulin increases plasma noradrenaline (NA) in these centrally induced effects reflect on plasma neuro normal humans. This effect is secondary to the stimula-transmitter levels is still unknown.…”
Section: Introductionmentioning
confidence: 99%